The Wistar Rat Parietal Lobe Cell And Pain Perception Changes After Frequent Of Mobile Phone Electromagnetic Wave Expose - Tamad, Fatiha Sri Utami; Budisulistyo, Trianggoro; Husni, Amin; Retnaningsih, Retnaningsih; Suryawati, Herlina; Suryadi, Suryadi (RSUP Dr. Kariadi, 2023)
Background: The increasing number of mobile phone users raises concerns about the effects. Mobile phone electromagnetic wave radiation harms pain perception due to granular cell changes in the cerebral parietal cortex. Objective: To determine the effect of exposure to electromagnetic waves mobile phone on pain perception due to changes in the granular cells of the cerebral parietal cortex Wistar rats. Methods: Experimental research using randomized posttest with control group design. Samples were 28 rats divided into 4 groups. The control group was not exposed, the treatment group was exposed to 2100 MHz electromagnetic waves for 2 hours/day with a distance of 3 cm for 15 days in treatment group 1, for 30 days in treatment group 2, and 45 days in treatment group 3. Measurement of pain onset using the hot method. Changes in pain threshold were taken from the difference in pain onset after exposure to before exposure. Granular cell changes in the cerebral parietal cortex were assessed from the total score with the provisions of normal cells (sumx0), hydropic degenerated cells (sumx1), and necrotic cells (sumx2). Results: The longer the exposure to mobile phones, the higher the pain threshold and the cerebral parietal cortex granular cell damage score. There was a significant difference in pain threshold and changes in cerebral parietal cortex granular cells between groups (p=0.000). There was a significant relationship between changes in the parietal cerebral cortex granular cells and pain threshold in Wistar rats exposed to electromagnetic waves (p=0.000). Conclusion: Exposure to mobile phone electromagnetic waves affects pain perception due to changes in the granular cells of the cerebral parietal cortex in wistar rats.